Non-invasive cardiac mapping for non-response in cardiac resynchronization therapy. (17th February 2019) - Strik, Marc; Ploux, Sylvain; Jankelson, Lior; Bordachar, Pierre
Abstract: Cardiac resynchronization therapy (CRT) is an effective intervention in selected patients with moderate-to-severe heart failure with reduced ejection fraction and abnormal left ventricular activation time. The non-response rate of approximately 30% has remained nearly unchanged since this therapy was introduced 25 years ago. While intracardiac mapping is widely used for diagnosis and guidance of therapy in patients with tachyarrhythmia, its application in characterization of the electrical substrate to elucidate the mechanisms involved in CRT response remain anecdotal. In the present review, we describe the traditional determinants of CRT response before presenting novel non-invasive techniques used for CRT optimization. We discuss efforts to identify the target electrical substrate to guide the deployment of pacing electrodes during the operative procedure. Non-invasive body surface mapping technologies such as ECG imaging or ECG belt enables prediction of acute and chronic CRT response. While electrical dyssynchrony parameters provide high predictive accuracy for CRT response when obtained during intrinsic conduction, their predictive value is less when acquired during CRT or LV-pacing. Key messages: Classic predictors of CRT response are female gender, NYHA class ≤ III, left ventricular ejection fraction ≥25%, QRS duration ≥150 ms and estimated glomerular filtration rate ≥60 mL/min. ECG-imaging is a comprehensive non-invasive mapping system which allows to express the amount of electrical asynchrony of a CRT candidate. Non-invasive body surface mapping technologies enables excellent prediction of acute and chronic CRT response before implantation. When performed during CRT or LV-pacing, the added value of these mapping systems remains unclear.